The interface between magic, plants and language - Koopman, A. (Southern African Humanities, 2013)
This article looks at the interface between magic, plants and language. After examining various conceptualisations of ‘magic’, the article focuses specifically on the manipulation of materia, particularly when accompanied by the ritual use of language. The emphasis in this part of the article is on incantations, recitation of spells, curses and similar utterances. Examples are given first from various cultures in Europe, then from Africa as a whole, and finally from Zulu culture. In examining these ‘words of power’ and the way they are used together with plants and other materia, the articles explores the notion that the name of a plant may often contain as much power as the plant itself. The article then goes on to look specifically at Zulu plant names, and concludes that in addition to their power in various forms of magic, such names may also have a mnemonic function, assisting traditional healers and diviners to remember not only the name of a particular plant, but its various functions in society as well.